Evaluation of Residential Areas Based on Geoecosystem Unit Characteristics in Banda Aceh - Juliansyah Harahap; Nazaruddin; Saufia Lailatur Rahmah; Arief Gunawan (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2026)
In 2005, the residential area in Banda Aceh covered 948.5 ha. Recently, the total residential footprint has expanded significantly to 2,982.12 ha. This study aims to evaluate existing residential land use based on geoecosystem characteristics to ensure alignment with land capacity, thereby enabling the formulation of appropriate zoning for residential development. A quantitative descriptive approach was employed, utilizing spatial analysis through matching and scoring techniques. This approach characterizes each geoecosystem unit within the study area and assesses them against standard land suitability criteria for settlements.